FERRAMENTA AUXILIAR PARA A ELABORAÇÃO DE PROJETO RESIDENCIAL DE ÁGUA FRIA - Cruz, Herbert; Almeida, Leandro Silva; Viana, Marina Ribeiro; Michelan, Denise de Gois Santos; Santos, Débora de Gois (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
When it draws up building design of cold water, it is necessary to follow activity flow to achieve the design conclusion successfully. It was found that there is a gap of the knowledge in the literature to join the cold water installations standard with the performance standard, for hydro sanitary system requirements. Thus, it was developed a tool to help in the preparation of cold water installations design that answer prescriptive and performance standards. This tool was built from the development of checklist, based on items cited in NBR 5626 and NBR 15575, in addition best practices of literature. With that, the items for checklist were defined, as: entry requirements, tank, booster set, distribution network, feeder, reduction of noise and vibrations, and product definition. These items were arranged in flowchart to observe the dependence or not with the later steps. For each item of the checklist, there are more specific subitem. With this development, it can be concluded that, the checklist becomes a facilitating tool for the development of the cold water installations designs.